Electrolyzed Hydrogen Water Protects against Ethanol-Induced Cytotoxicity by Regulating Aldehyde Metabolism-Associated Enzymes in the Hepatic Cell Line HepG2 - Satoshi Yano; Jinyun Wang; Shigeru Kabayama; Taichi Hara (MDPI AG, 2021)
Excessive alcohol consumption can cause multi-systemic diseases. Among them, alcoholic liver disease is the most frequent and serious disease. Electrolytic hydrogen water (EHW) is produced at the cathode during electrolysis of water and contains a large amount of molecular hydrogen and a low content of platinum nanoparticles with alkaline properties. In this study, we found that EHW inhibits ethanol-induced cytotoxicity by decreasing the intracellular acetaldehyde, a toxic substance produced by ethanol degradation, in hepatocyte cell lines HepG2. Analysis of the mechanism of action revealed that EHW inhibits the metabolism of ethanol to acetaldehyde by suppressing alcohol dehydrogenase. EHW also promotes the metabolism of acetaldehyde to acetic acid by activating aldehyde dehydrogenase, which plays to reduce aldehyde toxicity and intracellular reactive oxygen species in HepG2 cells. These functions were correlated with the concentration of molecular hydrogen in EHW, and were abolished by degassing treatment, suggesting that molecular hydrogen may contribute as a functional factor in the suppression of ethanol-induced hepatocellular damage. Furthermore, hydrogen water with high dissolved hydrogen molecule showed the same hepatocellular protective effect against ethanol as the EHW. These results suggest that EHW may be useful in the prevention of alcoholic liver disease.